1991
DOI: 10.3109/02688699109002888
|View full text |Cite
|
Sign up to set email alerts
|

Arachnoid cyst presenting as an extradural haematoma

Abstract: A case of extradural haematoma as the presenting feature of an arachnoid cyst is described. Haemorrhagic complications of arachnoid cysts are well known, but extradural haematoma is rare. A possible pathogenetic mechanism is proposed and the treatment of asymptomatic arachnoid cysts is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Interestingly, epidural haematoma in association with arachnoid cyst also has been described. 19 CONCLUSION Neurosurgeons are acquainted with ADPKD due to the increased incidence of cerebral aneurysms but the association between ADPKD, arachnoid cysts and CSDH has not been previously reported. Patients with ADPKD have an increased incidence of intracranial arachnoid cysts, which may predispose to the development of CSDH.…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, epidural haematoma in association with arachnoid cyst also has been described. 19 CONCLUSION Neurosurgeons are acquainted with ADPKD due to the increased incidence of cerebral aneurysms but the association between ADPKD, arachnoid cysts and CSDH has not been previously reported. Patients with ADPKD have an increased incidence of intracranial arachnoid cysts, which may predispose to the development of CSDH.…”
Section: Discussionmentioning
confidence: 88%
“…A literature review on the subject revealed only seven previously reported cases of EDH associated with the presence of ACs 1 3–7. We have performed a comparative analysis of the cases including the patient we have reported.…”
Section: Discussionmentioning
confidence: 99%
“…This presentation poses a surgical challenge, particularly if the space-occupying lesions are on the same side of the brain. A literature review on the subject revealed only seven reported cases of EDHs associated with the presence of AC 1 3–7. The management options are varied and depend on the unique patient presentation.…”
Section: Introductionmentioning
confidence: 99%
“…This situation has been described after open heart surgery Intradural arachnoid cyst formation may lead to cord compression [S]. Acute cord compression has been described secondary to an extradural haematoma formation following haemorrhage from an arachnoid cyst [6].…”
Section: Discussionmentioning
confidence: 99%